STUDY TO DEVELOP A CO-RELATIONSHIP BETWEEN WATER QUALITY AND LAND USE PATTERN AS INDEX OF RIVERINE WETLAND WITH STATISTICAL APPROACH - Roy, Malabika Biswas; Kumar, Abhishek; Ghosh, Arnab; Roy, Pankaj Kumar (Quaestiones Geographicae, 2020)
This investigation additionally recognizes partner cooperation issue and furthermore to moderate the real issue through subjective and quantitative appraisal of riverine wetland. Considering a floodplain wetland in rustic West Bengal, the concentration was extended to perceive the type of wetland capacities as per the idea of individuals’ contribution by group examination. Be that as it may, NDVI was connected to ponder the total weeds condition into the wetland to decide the connection between Water Quality Index (WQI) with Normalized Difference Vegatation Index (NDVI) and its impact on valuation. In ANOVA, which is computed by MINITAB programming, centrality level was lower than 0.05 for each case.